2013
DOI: 10.1177/0013124513494778
|View full text |Cite
|
Sign up to set email alerts
|

Sociocultural Boundary Formations in College Life and Intercultural Capital Development

Abstract: Based on selective findings from a qualitative study with first generation college students, this article presents the contradictory and complex ways in which the participants perceived sociocultural diversity on campus and their place within it. The students’ narratives both affirmed existing boundaries of social belonging based on the conventional categories of race, ethnicity, and social class and transcended them. Cross-border alliances were being built on campus at the same time that new boundaries were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
3
7
0
Order By: Relevance
“…The interactions with individuals who served as mentors to the FGC students gave them another source of personal connection to benefits associated with building a foundation of support. Oikonomidoy (2015) confirmed research about the benefits of mentorship and the connection to additional research from authors such as Fischer (2007) that pinpointed awareness to the values of FGC students needing to have a community of support to thrive in the collegiate environment.…”
Section: Mentoringsupporting
confidence: 54%
See 4 more Smart Citations
“…The interactions with individuals who served as mentors to the FGC students gave them another source of personal connection to benefits associated with building a foundation of support. Oikonomidoy (2015) confirmed research about the benefits of mentorship and the connection to additional research from authors such as Fischer (2007) that pinpointed awareness to the values of FGC students needing to have a community of support to thrive in the collegiate environment.…”
Section: Mentoringsupporting
confidence: 54%
“…Glass, Gesing, Hales, and Cong (2017) asserted that FGC students were at an academic disadvantage compared to their peers because of the lack of support for and awareness about the student population from faculty. Soria and Stebleton's (2012) research demonstrated that FGC students did not inherently possess the same levels of social capital, which is the ability to understand and use social networks for personal gain (Oikonomidoy, 2015) to assist with navigating the college environment. FGC students may have had difficulty connecting with faculty because they were intimidated and had no models for how to approach instructors (Willamson, Goosen, & Gonzalez, Jr., 2014).…”
Section: Significance Of the Research Questionmentioning
confidence: 99%
See 3 more Smart Citations